La filosofia e Dio (1919-2019) - Aime, Oreste (Teologia, 2020)
1919-2019 are dates that, however random, allow to outline a time in which the philosophical question about God was expressed in considerable moments and ways (especially after the two world wars). As regards to such historical route, we refer to the present by means of an oppositional comparison between two philosophical inquiries (S. Givone, P. Sloterdijk). In the last section, almost as a report, some clue points are highlighted (language, anthropo-logy and theo-logy) and their implications for the relationship between philosophy and theology.